Comparative studies of PID controller tuning methods on a DC-DC boost converter - Ibrahim, O. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents comparative studies of PID controller tuning methods on a DC-DC converter. A DC-DC boost converter was modelled using averaged state space method for controller design and dynamic analysis. PID controllers were designed using three different PID tuning methods; namely the Ziegler-Nichols frequency domain method, damped oscillation method and Good Gain method. The Matlab/Simulink was used to model and analyse the system transient response in terms of rise time, settling time, percentage overshoot and steady state error to step change input for their suitability in power supply design application. Among the three methods, the damped oscillation method demonstrated moderate fast rise and settling time with the advantage of lower overshoot to set point change. © 2016 IEEE.